An exploration of International Organization for Standardization/International Electrotechnical Commission (ISO/IEC) 17025 quality management in the Kansas Department of Agriculture Laboratory, and Food and Drug Administration (FDA) certification for a dairy analysis in a central laboratory - Jamma, Somia (My University, 2023)
ISO 17025 is the quality standard for testing and calibration laboratories. Food safety and quality management are implemented by good laboratory testing of food for microorganisms such as Escherichia coli and Salmonella. Food products can be a source of harmful biological and chemical factors for humans. During my applied practice experience at the KDA laboratory, I was involved in activities related to food safety, including identifying the results for dairy products and data analysis for public health improvement. It was found that the laboratory had monitored, controlled, and recorded environmental conditions in accordance with relevant specifications, methods, procedures, or instances where those conditions influence the validity of the results.
Keywords: ISO/IEC 17025; Quality Management; Kansas Department of Agriculture Laboratory; Food and Drug Administration (FDA) Certification; Dairy Analysis